RANCANG BANGUN SISTEM INFORMASI GEMPA MENGGUNAKAN RASPBERRY PI BERBASIS WEB - Ulil Albab; Rony Darpono; Fahreza Moch Revikansyah (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
Earthquake is one of the natural disasters that can occur without being used. Earthquakes originate from vibrations in the bowels of the earth that travel to the surface caused by fractures in the earth breaking and shifting violently. To prevent material and inmaterial losses, this research can be carried out by utilizing hardware technology in the form of Raspberry PI and Piezoelectric Sensors. Raspberry PI is a small single-board computer (SBC) used for electronics projects. Raspberry PI has 40 pins divided into two modes, namely BCM and BOARD. For making a Piezoelectric Sensor value reading program using the Python Programming Language. The results of reading the output of the Piezoelectric Sensor integrated with the Raspberry PI are in the form of a voltage value. The output of the voltage is sent to the Website Page in real time. The collection of output data can then be analyzed if there are indications of an earthquake. The trial form was carried out by dropping the weight of objects weighing 2 and 3 Kilograms with the drop points being 25 cm, 50 cm and 95 cm. The experiment was carried out 3 times based on weight and falling point. From the test results, the value of vibration on the piezoelectric sensor was obtained with the lowest value of 107787 and the highest 568785063. For the criteria for an earthquake or not, it is divided into 2 categories, namely weak or strong. If the vibration value is more than 880000 it is interpreted as a strong category otherwise if it is less than 880000 it is categorized as weak. The sensor reading results are then stored in the database and displayed on the Website Page.